Metascience: Guidelines for the Practitioner. Issue 4 (November 2019) - Turner, John R.; Brown, H. Quincy; Passmore, David L.; Nimon, Kim; Baker, Rose; Jeong, Shinhee; Flatt, Candace
The Problem: The trend in current research is to seek a statistically significant finding, one that provides a p value less than a predetermined alpha. Unfortunately, a large number of research studies have been identified as being nonreplicable along with having other shortcomings (low power, improper methodology, poor sample size) that reduce the rigor of a study's research findings. Additional techniques are needed beyond relying solely on a p value. The Solution: This article presents recommendations that Human Resource Development (HRD) scholars and scholar-practitioners can implement to improve the rigor of the discipline's research and practice. This article also provides guidelines (higher power, meta-analyses, low bias in large studies) of how to best avoid producing nonreplicability studies along with recommendations for the larger field, in this instance for scholars and scholar-practitioners in the social sciences. The Stakeholders: Scholars, scholar-practitioners, employees, and researchers who are impacted by changes in their environment due to less-than rigorous evidence-based research findings.